A Study of Road Safety Lead Agencies in Africa - Mitullah, Winnie (World Bank, Washington, DC, 2022)
This study of road safety lead agencies (RSLAs) in Africa takes place at an important time when serious injuries on roads are at the centre of discussions on sustainable development. RSLAs in Africa are considered to be critical vehicles for responding to road safety challenges, although how well they do this remains largely unknown. In literature, their functionality, complexity and autonomy has widely been assessed. However, there is limited attempt to link the management capacity of RSLAs to the observed road safety outcomes such as serious injuries and fatality reduction or reduction in the cost of road traffic crashes. Consequently, there is limited evidence as to whether or not lead agencies in Africa are achieving the intended goals of improving road safety status. This study sought to better understand these difficulties and the potential steps to success for RSLAs in Africa. It was commissioned by the African Development Bank and the World Bank and focuses on sixteen African countries. It is part of a global study of road safety lead agencies being undertaken by the World Health Organisation. The study is structured into four sections. Section 2 describes the two-phase methodology–desk study and preparation of the research instruments, data collection and analysis. This is followed in Section 3 by a discussion of the concept of lead agency, which lays the ground for presentation of the study results regarding lead agency performance in Section 4. Section 5 identifies lessons from the study and makes recommendations to improve lead agency performance.